ChemInform Abstract: Acidic Properties and Structure‐Activity Correlations of Solid Acid Catalysts Revealed by Solid‐State NMR Spectroscopy. Issue 23 (May 2016) - Zheng, Anmin; Li, Shenhui; Liu, Shang‐Bin; Deng, Feng
Abstract: Review: 40 refs.